ĐIềU CHế AXIT ALGINIC GIỡU CáC HợP PHầN AXIT POLYMANNURONIC Vỡ AXIT POLYGULURONIC BằNG PHƯƠNG PHáP THủY PHÂN - Kinh, Chu Dinh (Vietnam Journal of Chemistry, 2012)
The alginic acids with rich polymannuronic (MM) and rich polyguluronic (GG) composition have been prepared from Thua Thien Hue brown seaweeds by pH adjust method. The alginates were hydrolyzed by hydrochloride acid under hydrothermal treatment. The alginic acid fractions enriched in polymannuronic acid and polyguluronic acid were obtained by adjusting pH from 7 to 2. The obtained alginic acids were characterized by 1H-NMR and XRD. The obtained alginic acid with controllable structure has been expected feasible applications in medicine and agriculture.